Caracterização das transformações microestruturais em aços austeníticos da classe HP após surto de temperatura e envelhecimento artificial - Mendes, Matheus Campolina (2018)
Centrifugally cast stainless steel, particularly HP grade, has been well-established in the manufacture of radiant tubes due to its high temperature resistance. Recently, small contents of Nb and Ti were added to its chemical composition to increase microstructural stability, resulting in the micro-alloyed HP steels. Abnormal service conditions may restrict the feedstock flow, quickly leading to temperatures above 1000°C in localized regions along the tubes, these events are called temperature surges. During service, aging leads to fine secondary precipitation in the matrix and partial transformation of the primary NbC and (Nb,Ti)C to G-phase (Ni16Nb6Si7). After temperature surges, some uncertainties remain concerning the integrity of the tubes which haven’t collapsed due to overheating, and the possibility of their continued use, owing mainly to the extensive microstructural changes they display when compared to normally aged ones. In this context, the aim of this work is to characterize the effects of temperature surges, under both operational and simulated conditions and the effect of artificial aging at 900°C on the microstructure. This was acomplished via scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy mapping (EDS). Based on the microstructural modifications due to the different conditions studied in this work, it was concluded that 1050°C is the temperature that characterizes surges, leading to a partial solubilization of the secondary carbides and G-phase dissolution. After this event, a silicon and niobium enrichment in the interdendritic region and partial solubilization of the secondary carbides lead to an accelerated aging effect when compared to normal service conditions.